Epistemologi Filsafat dan Sains Persfektif Barat dan Islam dalam Dunia Pendidikan - Daulay, Lily Sardiani; Salminawati, Salminawati; Elmi, Nur; Parapat, Ilham Karim (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The words science and religion have always been controversial positions, even in the world of education. The purpose of this study is to determine the role of the epistemology of knowledge in Islamic and Western perspectives in the world of education. This research uses qualitative methods (library research), using data sources through articles and books. Based on the references that the researcher has read, the researcher found the result that epistemology has a very important role in the world of education, this is because epistemology is the mother of existing scientific findings. As for the epistemology of science from an Islamic perspective as explained by Al-Jabiri. According to Al-Jabiri, the epistemology of science is from an Islamic perspective, namely: 1) Bayani Epistemology 2) Burhan.